Toward efficient electrocatalytic oxygen evolution with a low concentration baking soda activated IrOx surface in a hydrothermal medium. (13th April 2022) - Hu, Yuling; Ma, Chenglong; Du, Gan; Gao, Hanqing; Tian, Xinlong; Yu, Huamei; Liao, Jianjun; Ge, Chengjun; Yang, Ji; Sun, Wei
Abstract : The presence of HCO3 − in a hydrothermal medium enables amorphous IrO x nanoparticles to possess a pseudo-crystalline morphology and further modifies the t2g orbitals, thus substantially increasing the OER catalytic activity. Abstract : Developing Ir-based catalysts with robust OER performance in a simple, green, and efficient way is critical for scaling up PEM electrolysis to megawatt levels. Here, we report that a low concentration of baking soda significantly increases the OER activity of IrO x nanoparticles and also achieves a yield of 100%. Specifically, the prepared amorphous IrO x affords 10 mA cm −2 with an overpotential of only 295 mV, which is even better than previously reported modified IrO2 . Moreover, a Sabatier-like relationship between the work function and the OER activity was clearly revealed and, combined with DFT calculations, the t2g orbitals in IrO x may play a more important role in enhancing the OER activity and they also can be regulated in the amorphous structure via creating more edge-shared IrO6 octahedrons. Atomic-resolution TEM shows that the presence of HCO3 − enables the surface atomic arrangement of amorphous IrO x to possess a pseudo-crystalline nature within a short range, which is responsible for the special changes in the orbital structure. According to the extensive experimental results, we believe that HCO3 − will likely play an important role in the preparation of Ir-based catalysts with robust OER performance, as baking soda outperforms conventional NaOH in terms of its activity, stability, and green nature.